Health education in Portuguese schools: the contribution of health and education sectors - Carvalho, Graça Simões de (2012)
Children and young people spend a large part of their lives in school. In this environment they eat, drink, smoke, fall in love, speak about AIDS and about drugs, face stress, and experience a wide range of emotions. It is during this formative stage of their lives that our students most need to experience education in their schools that is directed toward preventing physical and mental health problems. In this chapter, I describe and discuss the Portuguese system of school health education and health promotion, which is strongly inspired by the European Network of Health Promoting Schools (ENHPS) and Schools for Health in Europe (SHE). I begin by outlining and comparing the two main perspectives informing the general health education framework. The first perspective focuses on the biomedical model of health and the second on the social (holistic) model of health. I also pay special attention to the roles that the Portuguese health and education sectors play in implementing school health education and health promotion.